Model for the dielectric constant for 0-3 piezoelectric-polymer composites. (25th September 2016) - Tunkasiri, T.; Rujijanagul, G.; Intatha, U.; Pengpat, K.; Sutjarittangtham, K.; Eitssayeam, S.
ABSTRACT: The dielectric constants of PZT-polymer composites of the 0–3 connectivity employing the simple cube model (proposed by Pauer) showed considerable deviation between the theory to experimental observation. Banno modified the model by means of incorporating a geometric factor "n" into the model. However Banno selected the "n" value based on an attempt to match theory to experimental data. In this work we assume that the "n" value equal to the ratio of the Young modulus of the polymer to that of PZT and replace "n" by the ratio into the equation derived by Banno. Our expression compares very favorably with the sets of the experimental data for the PZT-polymer composites of the 0–3 connectivity.